SIMULATION MODELING OF THE URBAN TRANSPORT SYSTEM TAKEN INTO ACCOUNT OF CHANGES IN PASSENGER FLOW - Kudrаtоvа Mаlikа Mukhtоr kizi; Mamayev Gulom Ibrohimovich (Ta’lim innovatsiyasi va integratsiyasi, 2023)
The rapid growth of the urban population and the increase in its mobility cause a number of problems related to the development of transport in cities. Management of the transport system is one of the main components of the city's infrastructure, which provides the vital needs of the population.